As tessituras cotidianas que compõem as práticas de cuidado nas relações entre trabalhadores da saúde mental e usuários - Amorim, Rafaela Gomes (2014)
To research about the care production for the mental health workers on the day by day relationship of the work and with the users, it was used as methodological tools: the cartography - by considering the describing processes from 'one life' and the multiplicity that goes through the subject - and the narratives proposed for Walter Benjamin, as the way to tell stories about these processes that compose themselves on the care production. The Psychiatric Reform on Brazil was marked by criticism to the asylums modes, that were/are sicken and deny the desires and rights of the people that pass for the madness experience, interned or not. With the critic sight to this hospitalocentric model, many anti-asylum actors staged the creation of dispositives that traverse this way of care. The care on mental health passed by many transformations as Foucault (1982) shows, mainly with the rise of scientific knowledge, that appropriated the knowledge and the control of the bodies to deal with madness, what provided the crazy isolation. And, today, with the Psychiatric Reform, we have the challenge to continue the movement for deinstitutionalization of practices, knowledges and mental asylums, that cross the care work relations by means of captures, sensitive or not, that presentify themselves on the bodies, words and actions. Thus, it's necessary that these processes of ruptures to the asylum mode start in us, so that the subjectivity production and new modes of existence of the others expand in their (re)inventions. That's why the work creates itself all the time, and don't have a only model to care on mental health. However, it's important to note that the intervention must be guided on a ethic aesthetic-political and on the autonomy production of the subjects, so that the work don't be tutelary, but permits the statement of user's desires. The multiprofessional and transdisciplinary teams make all the difference on reception, on accompaniment and on the interventions with the users, the family and the mental health workers themselves. As a way of work device to produce care, the art and culture are seem as transformers of the modes of existence, as well as the leisure and the occupation of territory and of community wherein the users are inserted.